2006
DOI: 10.1159/000094291
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of TiF<sub>4</sub>, SnF<sub>2</sub> and NaF on Erosion of Enamel by Hydrochloric Acid in vitro Measured by White Light Interferometry

Abstract: The purpose of this in vitro study was to compare the protective effect of TiF4, SnF2 and NaF (all 0.5 M F) on the development of erosion-like lesions in human dental enamel. Four enamel specimens from each of 6 extracted molars were polished and embedded in epoxy resin. The enamel surfaces of 3 specimens from each tooth were treated with the different fluoride solutions for 2 min. Following fluoride treatments, the specimens were immersed in 0.01 M HCl (pH 2.0), for 2, 4 and 6 min in ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
100
1
52

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(162 citation statements)
references
References 36 publications
(21 reference statements)
9
100
1
52
Order By: Relevance
“…10 Apart from an acidic diet, erosion is also caused by frequent contact of the oral cavity 6,19 with HCl, being commonly observed in paediatric patients with gastro-oesophageal reflux. 5 The proposed protocol to simulate an episode of gastro-oesophageal reflux was adapted from the in vitro model of Hove et al 19 HCl, used in intrinsic erosion models, 20 is a strong acid, 21 which, in the presence of water, dissociates completely into hydrogen ions and chloride ions, removing the mineral surface. 22 Short-term acid exposures cause surface changes observed before the loss of tooth structure.…”
Section: Discussionmentioning
confidence: 99%
“…10 Apart from an acidic diet, erosion is also caused by frequent contact of the oral cavity 6,19 with HCl, being commonly observed in paediatric patients with gastro-oesophageal reflux. 5 The proposed protocol to simulate an episode of gastro-oesophageal reflux was adapted from the in vitro model of Hove et al 19 HCl, used in intrinsic erosion models, 20 is a strong acid, 21 which, in the presence of water, dissociates completely into hydrogen ions and chloride ions, removing the mineral surface. 22 Short-term acid exposures cause surface changes observed before the loss of tooth structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, its efficacy is still the object of controversy 1,2 , because little is known about the mechanism of action of fluoride on the prevention and/or control of dental erosion; erosive challenges are much more aggressive than cariogenic challenges and only a thin surface layer, partially demineralized, remains to provide structure for remineralization of eroded surface. 1 Successful results on the reduction of dental demineralization by erosive acids have been shown with polyvalent metal ion-containing products, such as stannous, in several in vitro studies 3,4,5,6,7 and confirmed by other in situ studies. 8,9,10,11 Authors have reported the use of tin-ion in different presentation, such as solutions, toothpastes, gels and varnishes.…”
Section: Introductionmentioning
confidence: 80%
“…14,16 In vitro and in situ studies show that pretreatment of enamel with tin-containing solutions can protect the enamel surface, inhibiting or reducing the erosive effect of acids through the formation of a superficial layer, containing Sn 2 OHPO 4 , Sn 3 F 3 PO 4 , Ca(SnF 3 ) 2 and CaF 2 -like precipitates, with a low dissolution rate. 1,3,4,12,13,24,32 It is believed that the treatment of the substrate with tin containing fluoride solutions favors the tin incorporation, and perhaps also the fluoride incorporation into the underlying enamel tissue, resulting in a broad structurally modified surface region, rich in tin and resistant to erosive acid challenge 28 . In addition, according to Hjortsjo et al 32 , the mechanism by which metal fluorides inhibitdental erosion is at least partially associated with the presence of HF (hydrofluoric acid) molecules that are capable of penetrating into the enamel and possibly form CaF 2 molecules in the inner enamel substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations